STRATEGI KEBIJAKAN LUAR NEGERI INDONESIA DALAM MENGHADAPI PERKEMBANGAN DINAMIKA GLOBAL DAN INTERNAL - Anwar, Dewi Fortuna (Jurnal Bestari, 2001)
There are some strategy of ferign politic of indonesia. Firstly, highlightening new national identity due to a polical transformation in indonesia that significantly divers to the past era that more otoriter and militeristic . the new indonesia identity as the biggest moslem democration state, in the frame of plurality and islam-moderate, as well as open economic system country. Secondly, indonesia needs professional public relation to market the good image of new indonesia both from the goverment and non-goeverment agent. And finally, democration value and humanright as a main and important subject in the world should also be a main public/ domestic practices.